Komunikasi dalam Pengasuhan AUD : Membangun Fondasi Perkembangan yang Sehat - Sri Mulyati; Shintya Anugrah Rahmadani; Mufaro’ah Mufaro’ah (Institut Nalanda, 2024)
In the communication process to achieve certain goals, there are three main components involved, namely the source of the message, the recipient of the message, and the message itself. In the early childhood education phase, it is important to improve communication by considering their developmental stage. What needs to be considered is the child's language progress, which will have a significant influence on communication strategies in this age group. One of the common mistakes that adult communicators make is a lack of understanding in communicating with children. Therefore, it is important to pay attention to communication barriers that may arise when interacting with them. There are three important things to pay attention to, namely using appropriate terms, maintaining good conversation, and giving clear instructions when you want to change the topic of conversation. By establishing effective communication, the growth and development of early childhood will occur optimally and healthily.